Subjective and Projective Measures of Thesis Writing Procrastination: Real World and The Sims World - Siaputra, Ide Bagus; Prawitasari, Johana E.; Hastjarjo, Thomas Dicky; Azwar, Saifuddin (Faculty of Psychology, Universitas Surabaya, 2011)
Although it has been studied since 1980s, the theoretical framework for procrastination has just been comprehensively developed about two decades later. This study applied Temporal Motivation Theory (TMT) as a theoretical framework to develop thesis writing procrastination instruments, using self report and Sim’s behavior observation methods. Self-report results of 232 undergraduate students have fulfilled psychometric norms, concerning either the reliability or validity aspects. Observation of Sim’s behaviors, performed by 48 students, also fulfilled some of the psychometric criteria. The discovery of contradictory patterns of academic activities in the real world against The Sims 2 World was perceived as evidences of basic value differences and manifestation of defense mechanism. Inclusion of subject’s responses on The Sims 2 game play pattern scale in the hierarchical linear regression equation improved the prediction power toward latency of thesis completion. Sekalipun telah dipelajari sejak 1980-an, kerangka kerja teoretis penunda-nundaan (prokrastinasi) baru tersusun secara komprehensif sekitar dua dekade kemudian. Penelitian ini menggunakan kerangka kerja teoretis Teori Motivasi Temporal (Temporal Motivation Theory/TMT) untuk mengembangkan alat ukur penunda-nundaan pengerjaan tugas akhir dengan laporan diri dan pengamatan perilaku sim. Hasil pengukuran laporan diri terhadap 232 mahasiswa telah memenuhi kaidah psikometris baik dari segi reliabilitas maupun validitas. Hasil pengamatan terhadap perilaku sim yang dikendalikan 48 mahasiswa juga telah memadai dari segi reliabilitas dan validitas. Ditemukannya pola berlawanan antara pengerjaan kegiatan akademik pada dunia nyata dan dunia The Sims 2, dimaknai sebagai bukti adanya perbedaan nilai dasar serta perwujudan mekanisme pertahanan diri. Penambahan prediktor berupa pola bermain The Sims 2 berhasil meningkatkan daya prediksi terhadap latensi penyelesaian skripsi.